The Development Of Heritage Building Conservation In George Town, Penang - Tan, Pei Yii. (Universiti Malaysia Sarawak (UNIMAS), 2018)
This research is to study on the development of The Development of Heritage Building Conservation in Georgetown, Penang. The method of the data collection for this research is through interview, observation and documentation. Total eight informants been interview. Researcher found out that the challenges on conservation in terms of on not only materials, time and financial but also to identify the ownership of the buildings.